Chitosan-starch composite Janus particles and preparation method and application thereof
The preparation of chitosan-starch composite Janus particles by ion gel method and Pickering emulsion template method was solved, and the preparation complexity and pollution of Janus particles in the prior art were achieved, and the biocompatible and degradable food-grade Janus particles were achieved. Its application in the food and medicine fields.
Patent Information
- Application Number
- CN202210882607.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-07-26
- Publication Date
- 2025-01-14
- Estimated Expiration
- 2042-07-26
AI Technical Summary
The application of existing Janus particles in the food and medicine fields is limited by the complexity of the preparation method and environmental pollution, and pure chitosan is difficult to effectively combine with starch to form particles.
Chitosan nanoparticles were prepared by ionic gel method, and combined with modified starch through the Pickering emulsion template method to form chitosan-starch composite Janus particles. A green and environmentally friendly method was adopted to combine the two by electrostatic action.
The preparation of biocompatible and degradable food-grade Janus particles under mild conditions is achieved, which simplifies operation, avoids pollution and toxicity in traditional methods, and expands the application of Janus particles in the food and medicine fields.
Smart Images

Figure CN115368591B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of modified starch, and particularly relates to chitosan-starch composite Janus particles and a preparation method and application thereof. Background Art
[0002] Janus particles are a new class of structures, describing an asymmetric material with two or more different chemical compositions or properties on its surface. To date, the versatility of synthetic polymers and inorganic materials has made them the main raw materials for synthesizing Janus particles in the fields of materials science and biomedicine. Janus particles show unique properties based on their binary design (such as surface activity, self-assembly, targeted release, self-propulsion, etc.), but the application of Janus particles in the food and pharmaceutical fields is still relatively small. The main reason is that among the commonly used preparation methods of Janus particles, microfluidic synthesis, current jet method, template-guided self-assembly method and other methods not only require special instruments and equipment, but also involve complex environments such as high temperature, electric field, organic solvents, etc., which will bring certain economic pressure and environmental pollution. Therefore, the application in this area needs further research and expansion. Natural biopolymers such as polysaccharides, such as starch and chitosan, are not only cheap and widely used, but also sustainable, biodegradable, safe and edible. Chitosan is the only natural polysaccharide with positive charge in nature, while starch is negatively charged in the aqueous system after esterification modification. The two can be combined in the aqueous system through electrostatic binding. However, due to the film-forming property of pure chitosan, it is not easy to combine well with starch to form particles. Summary of the invention
[0003] In order to solve the related problems, the primary purpose of the present invention is to provide a method for preparing chitosan-starch composite Janus particles. The method prepares chitosan nanoparticles by an ion gel method, and then prepares polysaccharide Janus particles combining chitosan nanoparticles and ODSA starch by a Pickering emulsion template method. The raw materials used in the method are green, environmentally friendly and pollution-free, and have good biocompatibility and biodegradability, and are edible.
[0004] Another object of the present invention is to provide chitosan-starch composite Janus particles obtained by the above preparation method. This is a new type of food-grade Janus particle material that is simply synthesized from natural polysaccharides.
[0005] Another object of the present invention is to provide an application of the chitosan-starch composite Janus particles.
[0006] In order to achieve the above-mentioned object of the invention, the present invention adopts the following technical solutions:
[0007] A method for preparing chitosan-starch composite Janus particles comprises the following steps:
[0008] (1) hydrophobically modifying starch by an esterifying agent to obtain hydrophobically modified starch;
[0009] (2) using the hydrophobically modified starch obtained in step (1) as a solid particle stabilizer for a Pickering emulsion and using a long-chain fatty acid as an oil phase, adding the two into water, mixing the three together evenly, and then homogenizing to form an emulsion; the homogenized emulsion is first refrigerated, then taken out and placed at room temperature for stabilization, thereby obtaining an O / W Pickering emulsion after the oil phase is solidified;
[0010] (3) dissolving chitosan in an acetic acid aqueous solution to form a chitosan solution; stirring, adjusting the pH to 4.5-5.2, and removing the residue of insoluble particles; then preheating, stirring, adding a sodium tripolyphosphate (TPP) aqueous solution, reacting, and obtaining a chitosan nanoparticle dispersion;
[0011] (4) adding the chitosan nanoparticle dispersion to the Pickering emulsion obtained in step (2) to react to obtain a mixed system of the two, separating the excess chitosan nanoparticle dispersion, then adding distilled water, ultrasonicating, centrifuging, and repeating the above steps, and discarding the supernatant of the last centrifugation to obtain the chitosan-starch composite Janus particles.
[0012] Preferably, the starch in step (1) is any one or more combinations of quinoa starch, rice starch, and amaranth starch.
[0013] Preferably, the esterifying agent in step (1) is any one or more combinations of octadecenylsuccinic anhydride (ODSA), hexadecenylsuccinic anhydride (HDSA), tetradecenylsuccinic anhydride (TDSA), and dodecenylsuccinic anhydride (DDSA).
[0014] Preferably, the mass range of the esterification agent in step (1) is 5% to 30% of the mass of the starch; further preferably, the mass range of the esterification agent is 10% to 20% of the mass of the starch.
[0015] Preferably, step (1) is carried out at 35±5°C.
[0016] Preferably, the reaction time of the hydrophobic modification in step (1) is controlled within 3 hours.
[0017] Preferably, the long-chain fatty acid in step (2) is any one or more combinations of lauric acid, myristic acid, and capric acid.
[0018] Preferably, the mixed system in step (2) contains 30-150 mg of hydrophobic starch and 100-1500 mg of long-chain fatty acids per unit; further preferably, the mixed system contains 50-100 mg of hydrophobic starch and 500-1000 mg of long-chain fatty acids per unit.
[0019] Preferably, the mass ratio of the long-chain fatty acids to water in step (2) is in the range of 1:3 to 1:12; further preferably, the mass ratio of the long-chain fatty acids to water is in the range of 1:5 to 1:10.
[0020] Preferably, the temperature condition for uniform mixing in step (2) is 44-52°C; further preferably, the temperature condition for uniform mixing is 46-50°C.
[0021] Preferably, the uniform mixing in step (2) is achieved by ultrasound and vortexing; further preferably, the ultrasound time is 5 to 15 minutes.
[0022] Preferably, the homogenization speed in step (2) is 10000-16000 rpm and the time is 1-5 min; further preferably, the homogenization speed is 13000-15000 rpm and the time is 1-3 min.
[0023] Preferably, the refrigeration temperature in step (2) is 0-4°C and the time is 30±5min.
[0024] Preferably, the stabilization time in step (2) is 60±5 min.
[0025] Preferably, the room temperature in the present invention refers to 20-30°C.
[0026] Preferably, the chitosan in step (3) is any one or more combinations of low molecular weight chitosan (MW<50000), medium molecular weight chitosan (MW=50000-100000), and high molecular weight chitosan (MW>100000).
[0027] Preferably, the concentration of the acetic acid aqueous solution in step (3) is 0.1 to 0.8 mg / mL; further preferably, the concentration of the acetic acid aqueous solution is 0.2 to 0.4 mg / mL.
[0028] Preferably, the amount of water-soluble chitosan used in step (3) is calculated based on its concentration in the system of 0.1 to 1.0 mg / mL; further preferably, the amount of water-soluble chitosan used is calculated based on its concentration in the system of 0.3 to 0.8 mg / mL.
[0029] Preferably, the stirring time in step (3) is 1 to 18 hours; further preferably, the stirring time is 3 to 12 hours.
[0030] Preferably, the pH in step (3) is adjusted to 4.7-4.8.
[0031] Preferably, the reagent used for adjustment in step (3) is sodium hydroxide solution; further preferably, the concentration of the sodium hydroxide solution is 10% (m / v).
[0032] Preferably, the removal of the insoluble particles in step (3) is achieved by a syringe filter; further preferably, the pore size of the syringe filter is 0.45 μm.
[0033] Preferably, the preheating temperature in step (3) is 25-70°C and the time is 5-40 min; further preferably, the preheating temperature is 40-60°C and the time is 10-20 min; further preferably, the preheating is achieved by a water bath.
[0034] Preferably, the stirring speed after preheating in step (3) is 200 to 1000 rpm; more preferably, the stirring speed is 600 to 800 rpm.
[0035] Preferably, the concentration of the sodium tripolyphosphate aqueous solution in step (3) is 0.1-1.0 mg / mL; further preferably, the concentration of the sodium tripolyphosphate aqueous solution is 0.3-0.8 mg / mL; further preferably, the sodium tripolyphosphate aqueous solution is passed through a syringe filter before use, and the pore size of the syringe filter is 0.22 μm.
[0036] Preferably, in step (3), based on the volume of the chitosan solution after removing the residue of insoluble particles being 20 mL, the amount of sodium tripolyphosphate aqueous solution added is 2 to 10 mL; further preferably, the amount of sodium tripolyphosphate aqueous solution added is 4 to 6 mL.
[0037] Preferably, the reaction time in step (3) is 5 to 60 min; further preferably, the reaction time is 10 to 30 min.
[0038] Preferably, the chitosan nanoparticle dispersion in step (4) is diluted 3.3 to 100 times before use; further preferably, the chitosan nanoparticle dispersion is diluted 5 to 50 times before use.
[0039] Preferably, in step (4), the volume ratio of the chitosan nanoparticle dispersion to the Pickering emulsion is 1:3 to 10:1; further preferably, the volume ratio of the chitosan nanoparticle dispersion to the Pickering emulsion is 2:3 to 20:3.
[0040] Preferably, the reaction time in step (4) is 5 to 60 min; further preferably, the reaction time is 10 to 30 min.
[0041] Preferably, the separation of excess chitosan nanoparticle dispersion in step (4) is achieved by centrifugation; further preferably, the centrifugation time is 1 to 7 minutes; further preferably, the centrifugation time is 3 to 5 minutes.
[0042] Preferably, the number of repetitions in step (4) is 1 to 7 times; more preferably, the number of repetitions is 3 to 5 times.
[0043] Chitosan-starch composite Janus particles are obtained by the preparation method.
[0044] Application of the chitosan-starch composite Janus particles in the food or medicine fields.
[0045] The present invention is based on the following foundations:
[0046] (1) Small quinoa starch particles with a particle size of 1-3 μm can stabilize the Pickering emulsion well. After being hydrophobically modified by succinic anhydride, they can be more stably adsorbed on the oil-water interface of the Pickering emulsion.
[0047] (2) The long-chain fatty acid selected as the oil phase is non-toxic and harmless, and is solid at room temperature, and has a melting point higher than room temperature and lower than the gelatinization temperature of starch. The oil phase is first heated to the melting point to make it liquid, and then the O / W emulsion is stabilized at room temperature after preparation. At this time, the oil phase solidifies, and part of the starch granules stabilized at the Pickering interface are locked by the solidified oil phase, while part is still exposed to the water phase, making it possible to carry out asymmetric modification at this time.
[0048] (3) Chitosan nanoparticles are prepared, and the positive charge of the natural polysaccharide chitosan and the negative charge of starch are utilized to combine the two through electrostatic interaction, thereby completing the asymmetric modification of the starch surface exposed to the aqueous phase by chitosan nanoparticles.
[0049] (4) After the modification is completed, the solidified oil phase is heated to the melting point and becomes liquid again. After successful demulsification, the starch particles can be easily extracted from it to obtain chitosan-starch composite Janus particles.
[0050] The present invention has the following advantages and effects compared with the prior art:
[0051] 1) Using Pickering emulsion as a template to synthesize Janus particles, the conditions are mild and the operation is simple;
[0052] 2) The selected oil phase is a long-chain fatty acid, which is non-toxic and harmless, avoiding the toxicity and pollution caused by the traditional emulsion organic phase as the oil phase, which is more green and environmentally friendly, allowing this technology to be used in food;
[0053] 3) For the first time, Janus particles combining two polysaccharides were prepared, which can combine the characteristics and advantages of two biological macromolecules and further expand the application of Janus particles in the food or medical fields. BRIEF DESCRIPTION OF THE DRAWINGS
[0054] Figure 1 The confocal microscope images of the chitosan nanoparticles obtained in Example 1 combined with the Pickering emulsion; wherein A is a picture taken at an excitation wavelength of 488 nm; B and C are pictures taken after superposition of two channels at excitation wavelengths of 488 nm and 633 nm, and the green ones after excitation are chitosan nanoparticles, and the red ones after excitation are starch;
[0055] Figure 2 This is a scanning electron micrograph of the Janus particles composited with two starch-based polysaccharides modified by chitosan nanoparticles obtained in Example 1; wherein A, B, and C are Janus particles prepared by mixing chitosan nanoparticles with Pickering emulsion at a volume ratio of 2:3, 5:3, and 10:3, respectively.
[0056] Figure 3 The confocal microscope image of the Janus particles of two polysaccharides based on starch modified by chitosan nanoparticles obtained in Example 1; wherein A (scale 0-5 μm) and B (scale 0-2.5 μm) are images taken at different magnifications after superposition of two channels at excitation wavelengths of 488 nm and 633 nm, and those that appear green after excitation are chitosan nanoparticles, and those that appear red after excitation are starch;
[0057] Figure 4 TG thermogravimetric curves of the three particles obtained in Example 1. DETAILED DESCRIPTION
[0058] The present invention is further described in detail below in conjunction with examples and drawings, but the embodiments of the present invention are not limited thereto.
[0059] Example 1
[0060] The chitosan-starch composite Janus particles were prepared in the following steps:
[0061] (1) Quinoa starch was hydrophobically modified at 35°C using octadecene succinic anhydride (ODSA) as an esterifying agent, the mass of the esterifying agent was 15% of the mass of the starch, and the reaction time was controlled within 3 hours to prepare ODSA-modified ODSA starch.
[0062] (2) 75 mg of ODSA starch was used as the solid particle stabilizer of the Pickering emulsion, and 750 mg of lauric acid was used as the oil phase. The two solids were added to 5 mL of water, and then the whole system was ultrasonically dispersed evenly in a water bath at 46°C for 10 min, and then the whole system was vortexed to mix the three evenly, and then homogenized at 14000 rpm in a water bath at 46°C for 2 min. The homogenized emulsion was immediately placed in the upper layer of a refrigerator at 0-4°C for 30 min, and then taken out and stabilized at room temperature for 1 h to obtain an O / W Pickering emulsion after the lauric acid oil phase was solidified.
[0063] (3) Low molecular weight chitosan was dissolved in an aqueous acetic acid solution to form a 0.5 mg / mL chitosan solution, and the concentration of the acetic acid solution was 0.3 mg / mL. The chitosan solution was stirred at room temperature for 6 h using magnetic stirring, and the pH was adjusted to 4.7-4.8 with a 10% sodium hydroxide solution, and then the chitosan solution was passed through a syringe filter (pore size 0.45 μm) to remove the residue of insoluble particles. TPP (sodium tripolyphosphate) was dissolved in distilled water at a concentration of 0.5 mg / mL and passed through a syringe filter (pore size 0.22 μm). 20 mL of chitosan solution in a 100 mL beaker was preheated in a 50°C water bath for 15 min, and then the beaker was stirred at 700 rpm, 5 mL of TPP solution was added to the chitosan solution, and the reaction was carried out for 20 min to obtain a dispersion of chitosan nanoparticles.
[0064] (4) Add the chitosan nanoparticle dispersion diluted 30 times into the Pickering emulsion at a volume ratio of 10:9, and react for 20 minutes to obtain a mixed system of the two. Figure 1 As shown in the figure, after the oil phase of the Pickering emulsion template solidifies, part of the starch granule surface is locked inside the oil phase, and part of the surface is exposed to the water phase. At this time, the chitosan nanoparticles only modify the surface of the starch granules exposed to the water phase, and do not penetrate into the oil phase, thus achieving the purpose of asymmetric modification.
[0065] (5) The mixture was centrifuged to separate the excess chitosan nanoparticle dispersion, and then distilled water was added. The mixture was ultrasonicated at 50°C for 10 min, and then centrifuged at 4000 rpm for 4 min. The above steps were repeated 4 times. The supernatant of the last centrifugation was discarded to obtain chitosan-starch composite Janus particles. Photograph of the prepared Janus particles under a laser confocal microscope Figure 3 As shown in the figure, only a part of the surface of the chitosan-starch Janus particles is covered with chitosan nanoparticles. The scanning electron microscopy images further verified the successful preparation of asymmetric chitosan-starch Janus particles. The scanning electron microscopy results of the Janus particles prepared at different volume ratios are shown in Figure 2 shown.
[0066] The TG thermogravimetric curves of the three particles obtained in this example are as follows: Figure 4 As shown in the figure, the mass retention rates of the original ODSA starch, Janus ODSA starch, and fully covered ODSA starch particles at a temperature of 500°C were 12.78%, 23.77%, and 27.31%, respectively, which proves that only a part of the chitosan-starch Janus particles are attached with chitosan nanoparticles, so the final mass retention rate is between the two.
[0067] The DSC data results of the three particles obtained in this example are shown in Table 1. As can be seen from the table, with the combination of chitosan nanoparticles and ODSA starch, the endothermic enthalpy of the particles increases significantly, and the endothermic enthalpy of the Janus particles is between the original ODSA starch and the fully covered starch, proving the asymmetric structure of the Janus particles.
[0068] Table 1. DSC data results of three kinds of particles
[0069]
[0070] Example 2
[0071] The chitosan-starch composite Janus particles were prepared in the following steps:
[0072] (1) hydrophobically modifying quinoa starch with hexadecenylsuccinic anhydride (HDSA) as an esterifying agent at 35° C., wherein the mass of the esterifying agent is 10% of the mass of the starch, and the reaction time is controlled within 3 h to prepare HDSA-modified HDSA starch;
[0073] (2) 50 mg HDSA starch was used as the solid particle stabilizer of the Pickering emulsion, and 500 mg capric acid was used as the oil phase. The two solids were added to 5 mL of water, and then the whole system was ultrasonically dispersed evenly in a water bath at 48°C for 10 minutes, and then the whole system was vortexed to mix the three evenly, and then homogenized at 13000 rpm in a water bath at 48°C for 1 minute. The homogenized emulsion was immediately placed in the upper layer of a refrigerator at 0-4°C for 30 minutes, and then taken out and stabilized at room temperature for 1 hour to obtain an O / W type Pickering emulsion after the capric acid oil phase was solidified.
[0074] (3) Dissolve the medium molecular weight chitosan in an aqueous acetic acid solution to form a 0.3 mg / mL chitosan solution, and the concentration of the acetic acid solution is 0.2 mg / mL. Stir the chitosan solution at room temperature for 3 h using magnetic stirring, and adjust the pH to 4.7-4.8 with a 10% sodium hydroxide solution, and then pass the chitosan solution through a syringe filter (pore size 0.45 μm) to remove the residue of insoluble particles. TPP (sodium tripolyphosphate) is dissolved in distilled water at a concentration of 0.3 mg / mL and passed through a syringe filter (pore size 0.22 μm). Preheat 20 mL of chitosan solution in a 100 mL beaker in a 40°C water bath for 10 min, then stir the beaker at 600 rpm, add 4 mL of TPP solution to the chitosan solution, and react for 10 min to obtain a dispersion of chitosan nanoparticles.
[0075] (4) A chitosan nanoparticle dispersion diluted 50 times was added to the Pickering emulsion at a volume ratio of 2:3, and the mixture was reacted for 10 minutes to obtain a mixed system of the two.
[0076] (5) The mixture was centrifuged to separate the excess chitosan nanoparticle dispersion, and then distilled water was added. The mixture was ultrasonicated at 35°C for 10 min, and then centrifuged at 4000 rpm for 3 min. The above steps were repeated 3 times, and the supernatant was discarded to obtain chitosan-starch composite Janus particles.
[0077] Example 3
[0078] The chitosan-starch composite Janus particles were prepared in the following steps:
[0079] (1) hydrophobically modifying quinoa starch with tetradecene succinic anhydride (TDSA) as an esterifying agent at 35° C., wherein the mass of the esterifying agent is 20% of the mass of the starch, and the reaction time is controlled within 3 h, to prepare TDSA-modified TDSA starch;
[0080] (2) 100 mg of TDSA starch was used as the solid particle stabilizer of the Pickering emulsion, and 1000 mg of myristic acid was used as the oil phase. The two solids were added to 5 mL of water, and then the whole system was ultrasonically dispersed evenly in a water bath at 50°C for 10 minutes, and then the whole system was vortexed to mix the three evenly, and then homogenized at 15000 rpm in a water bath at 50°C for 3 minutes. The homogenized emulsion was immediately placed in the upper layer of a refrigerator at 0-4°C for 30 minutes, and then taken out and stabilized at room temperature for 1 hour to obtain an O / W type Pickering emulsion after the myristic acid oil phase was solidified.
[0081] (3) High molecular weight chitosan was dissolved in an aqueous acetic acid solution to form a 0.8 mg / mL chitosan solution, and the concentration of the acetic acid solution was 0.4 mg / mL. The chitosan solution was stirred at room temperature for 12 h using a magnetic stirrer, and the pH was adjusted to 4.7-4.8 with a 10% sodium hydroxide solution, and then the chitosan solution was passed through a syringe filter (pore size 0.45 μm) to remove the residue of insoluble particles. TPP (sodium tripolyphosphate) was dissolved in distilled water at a concentration of 0.8 mg / mL and passed through a syringe filter (pore size 0.22 μm). 20 mL of chitosan solution in a 100 mL beaker was preheated in a 60°C water bath for 20 min, and then the beaker was stirred at 800 rpm, 6 mL of TPP solution was added to the chitosan solution, and the reaction was carried out for 30 min to obtain a dispersion of chitosan nanoparticles.
[0082] (4) Add a chitosan nanoparticle dispersion diluted 5 times to the Pickering emulsion at a volume ratio of 20:3 and react for 30 minutes to obtain a mixed system of the two.
[0083] (5) The mixture was centrifuged to separate the excess chitosan nanoparticle dispersion, and then distilled water was added. The mixture was ultrasonicated at 52°C for 10 min, and then centrifuged at 4000 rpm for 5 min. The above steps were repeated 5 times, and the supernatant was discarded to obtain chitosan-starch composite Janus particles.
[0084] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the described embodiments. Any other changes, modifications, substitutions, combinations, and simplifications made without departing from the spirit and principles of the present invention shall be equivalent replacement methods and shall be included in the protection scope of the present invention.
Claims
1. A method for preparing chitosan-starch composite Janus particles, characterized in that: The steps include: (1) hydrophobically modifying starch by using an esterifying agent to obtain hydrophobically modified starch; (2) using the hydrophobically modified starch obtained in step (1) as a solid particle stabilizer of the Pickering emulsion and using a long-chain fatty acid as the oil phase, adding the two into water, mixing the three together evenly, and then homogenizing into an emulsion; the homogenized emulsion is first refrigerated, then taken out and placed at room temperature for stabilization, thereby obtaining an O / W type Pickering emulsion after the oil phase is solidified; (3) dissolving chitosan in an acetic acid aqueous solution to form a chitosan solution; stirring, adjusting the pH to 4.5-5.2, and removing the residue of insoluble particles; then preheating, stirring, adding a sodium tripolyphosphate aqueous solution, reacting, and obtaining a chitosan nanoparticle dispersion; (4) adding the chitosan nanoparticle dispersion to the Pickering emulsion obtained in step (2) to react and obtain a mixed system of the two, separating the excess chitosan nanoparticle dispersion, and then adding distilled water, ultrasonicating, centrifuging, and repeating the above steps, and discarding the supernatant of the last centrifugation to obtain the chitosan-starch composite Janus particles.
2. The method for preparing chitosan-starch composite Janus particles according to claim 1, characterized in that: The starch in step (1) is any one or more combinations of quinoa starch, rice starch, and amaranth starch; The esterifying agent in step (1) is any one or more of octadecenyl succinic anhydride, hexadecenyl succinic anhydride, tetradecenyl succinic anhydride, and dodecenyl succinic anhydride; The mass range of the esterifying agent in step (1) is 5% to 30% of the mass of the starch.
3. The method for preparing chitosan-starch composite Janus particles according to claim 1, characterized in that: The long-chain fatty acid in step (2) is any one or more combinations of lauric acid, myristic acid, and capric acid; The mixed system in step (2) contains 30-150 mg of hydrophobic starch and 100-1500 mg of long-chain fatty acid per unit; The mass ratio of the long-chain fatty acid to water in step (2) is in the range of 1:3 to 1:
12.
4. The method for preparing chitosan-starch composite Janus particles according to claim 2 or 3, characterized in that: The mass range of the esterification agent in step (1) is 10% to 20% of the mass of the starch; The mixed system in step (2) contains 50-100 mg of hydrophobic starch and 500-1000 mg of long-chain fatty acid per unit; The mass ratio of the long-chain fatty acid to water in step (2) is in the range of 1:5 to 1:10; Step (1) is carried out at 35±5°C; The reaction time of the hydrophobic modification in step (1) is controlled within 3 hours; The temperature condition for uniform mixing in step (2) is 44-52°C; The uniform mixing in step (2) is achieved by ultrasound and vortexing; the ultrasound time is 5 to 15 minutes; The homogenization speed in step (2) is 10000-16000 rpm and the time is 1-5 min; The refrigeration temperature in step (2) is 0-4°C and the time is 30±5 min; The stabilization time described in step (2) is 60±5 min.
5. The method for preparing chitosan-starch composite Janus particles according to claim 1, characterized in that: The chitosan in step (3) is any one or more combinations of low molecular weight chitosan, medium molecular weight chitosan, and high molecular weight chitosan; The concentration of the acetic acid aqueous solution in step (3) is 0.1-0.8 mg / mL; The amount of chitosan used in step (3) is calculated based on its concentration in the system of 0.1 to 1.0 mg / mL; The preheating temperature in step (3) is 25 to 70°C and the preheating time is 5 to 40 minutes; The concentration of the sodium tripolyphosphate aqueous solution in step (3) is 0.1-1.0 mg / mL; In step (3), the amount of sodium tripolyphosphate aqueous solution added is 2 to 10 mL based on the volume of the chitosan solution after removing the insoluble particles as 20 mL; The reaction time in step (3) is 5 to 60 min.
6. The method for preparing chitosan-starch composite Janus particles according to claim 5, characterized in that: The concentration of the acetic acid aqueous solution in step (3) is 0.2-0.4 mg / mL; The amount of chitosan used in step (3) is calculated based on its concentration in the system of 0.3-0.8 mg / mL; The preheating temperature in step (3) is 40-60°C and the preheating time is 10-20 min; The concentration of the sodium tripolyphosphate aqueous solution in step (3) is 0.3-0.8 mg / mL; In step (3), based on the volume of the chitosan solution after removing the insoluble particles being 20 mL, the amount of the sodium tripolyphosphate aqueous solution added is 4 to 6 mL; The reaction time in step (3) is 10 to 30 min. The stirring time in step (3) is 1 to 18 h; In step (3), the pH is adjusted to 4.7-4.8; The reagent used for adjustment in step (3) is sodium hydroxide solution; The stirring speed after preheating in step (3) is 200 to 1000 rpm.
7. The method for preparing chitosan-starch composite Janus particles according to claim 1, characterized in that: The chitosan nanoparticle dispersion in step (4) is diluted 3.3 to 100 times before use; The volume ratio of the chitosan nanoparticle dispersion to the Pickering emulsion in step (4) is 1:3 to 10:1; The reaction time in step (4) is 5 to 60 min.
8. The method for preparing chitosan-starch composite Janus particles according to claim 7, characterized in that: The chitosan nanoparticle dispersion in step (4) is diluted 5 to 50 times before use; The volume ratio of the chitosan nanoparticle dispersion to the Pickering emulsion in step (4) is 2:3 to 20:3; The reaction time in step (4) is 10 to 30 min; The separation of excess chitosan nanoparticle dispersion in step (4) is achieved by centrifugation; the centrifugation time is 1 to 7 minutes; The number of repetitions in step (4) is 1 to 7 times.
9. A chitosan-starch composite Janus particle, characterized in that: The method is obtained by the preparation method described in any one of claims 1 to 8.
10. Use of the chitosan-starch composite Janus particles according to claim 9 in the food field.
Citation Information
Cited By
Food-grade anisotropic nanoparticles with double-domain partition structure as well as preparation method and application of food-grade anisotropic nanoparticles
CN121817457A